Phytochemical characterization of some herbal concoctions made and sold in Lesotho that are claimed to treat COVID-19 and related respiratory ailments - Khoabane, Reitumetse; Mhlongo, Msizi I; George, Mosotho J. (Orapuh Journal, 2023)
IntroductionSafety and efficacy of herbal products is a major health concern in countries with poor or no regulation regarding the ingredients, dosages, side effects, and contraindications of these traditional medicines. Herein we report the phytochemical characterization of some commercially available plant-derived concoctions in Lesotho, providing a possible scientific basis for the function and possible safety of such concoctions, based on the determined chemical compounds with the aid of documented phytochemical studies on medicinal plants. PurposeThe purpose of this study was to use the documented phytochemical studies of medicinal plants in Lesotho and other parts of the world as a basis to study and characterize the commercially available traditional and herbal remedies that are claimed to fight respiratory ailments including those related to COVID-19 infection in Lesotho – Southern Africa. Methods Phytochemical screening was carried out on three herbal concoctions produced and sold in Lesotho using simple wet chemistry procedures. Solvent microextraction was carried out followed by gas chromatography and mass spectrometry for the purpose of qualitative analysis of the volatile organic compounds (VOCs). ResultsAt least 5 major phytochemicals in each concoction were obtained with tannins and flavonoids quantified spectrophotometrically. One concoction (ROCK) had a total tannin content of about 75 µg/mL and a total flavonoid content of 300 µg/mL relative to the other plants averaging 20 and 50 µg/mL respectively. GC-MS analyses of the concoctions revealed the varying degrees of presence of VOCs with one showing hardly any peaks on the chromatogram indicating that either the concoction was not made from plants, or the VOCs had almost completely been lost during the processes of preparation. The other compounds detected, namely, benzoic acid (48% in ROCK), phthalic acid ester (detected in all concoctions), and glycerine, are consequent on processing indicating the importance of processing in the safety of processed plants as some of these are hazardous beyond certain thresholds.Conclusions The tested products show variable amounts of phytochemicals with ROCK showing more volatiles than the other two products. The detected phytochemicals indicate that the products are indeed plant derived while the VOCs profile indicates difference in treatment. The detection of phthalates suggests the importance of testing these products for the presence of unwanted chemicals.